View the Chinese Products Exhibition in Tokyo and Osaka 1955 through the Archives from the Archive Library of Ministry of Foreign Affairs of China: Arrangement, Obstruction and Gains - Piyasirikul, Kampol (Journal of Sinology (วารสารจีนวิทยา), 2009)
By focusing on using the archives from the archive library of the Ministry of Foreign Affairs of China, this article has discussed and analyzed in brief about the extent to which New China sent its delegation to Tokyo and Osaka Japan in 1955 to hold the Chinese Products Exhibition. The writer has divided the content of this article into four parts: its historical background, the arrangement of the exhibition, the obstruction of the exhibition and the gains of the exhibition. The writer believes, from the aspect of economy and trade, that this article can illustrate Sino-Japanese non-governmental relation after New China was founded through studying of the process of holding these two Chinese Products Exhibitions.